Lectura y lectores en la España de la Ilustración: el caso de la literatura artística - Crespo Delgado, Daniel (Cuadernos de Historia Moderna, 2007)
Last years many studies have aroused about reading and readers during the second half of the XVIIIth century in Spain. The main objectives of this investigation are to define possible changes took place and its relation with the enlightened movement. From the suggestive perspectives have been open, we will analyze the public of the artistic literature during the second half of the XVIIIth century and the beginnings of the XIXth century. This is an unknown aspect until now which will help to draw precisely aspects of reading in Spain in that decisive period.